Anne of Green Gables [videorecording (DVD)] : the continuing story - Scaini, Stefan; Follows, Megan; Crombie, Jonathan; Daddo, Cameron (Sullivan Entertainment, 2002)
Now in her twenties, Anne returns to Avonlea for the first time since Marilla's death. Gilbert is offered a position in New York and he convinces Anne to go with him. Big city life isn't what they expected. After her script is stolen, they travel from New York to the war effort in Europe and they eventually return to Prince Edward Island.